Splenic infarct: a rare complication in extensively drug-resistant Salmonella typhi - Fatima, Arfa; Yousuf, Fatimah Sireen; Khan, Muhammad Arbaz Arshad; Arshad, Ainan (Journal of the Pakistan Medical Association, 2026)
Enteric fever is a common systemic infection characterised by high grade fever and variable gastrointestinal symptoms. Splenic abscesses, thrombosis, and infarcts are uncommon complications. We report a case of splenic infarction in a young female presenting with persistent fever and abdominal pain. Her blood culture showed drug-resistant Salmonella Typhi (S.Typhi). Due to persistent abdominal pain, abdominal imaging was performed, which revealed multiple splenic infarcts. Treatment with appropriate antibiotics led to complete resolution of symptoms. This case emphasises the importance of timely diagnosis with relevant investigations for the effective management of an unusual presentation of enteric fever. Keywords: Enteric fever, splenic infarct, XDR Salmonella typhi.